Studi Kualitatif Fenomenologi Pengalaman Hidup Pasien Pasca Kolostomi di Wilayah Jawa Barat - La Rangki; Kusman Ibrahim; Aan Nur'aini (Halu Oleo University, 2018)
ABSTRACTPatient with colostomy followed colorectal has been cancer increasing significantly in Indonesia. Colostomy caused not only physical problems but also psychological and social problems. Health care profesional, especially nurses need to provided hollistic care services to the patients after colostomy. Study with Qualitative method to describe the live experience of the colostomy patient was important. This study was a phenomenological qualitative approach . Data obtained with in-depth interviews to 8 informants consisting of 5 men and 3 women, aged between 30-73 years. The length of time living with a colostomy between 4 months to 6 years. Data were analyzed by using Colaizzi method. Themes emerged from this study: ;sources of support;live with a colostomy; live adaptation; the burdens living with a colostomy. Living with a colostomy faced problems including the limitation to fulfill their needs, psychosocial changes, spiritual distress, and economic problems. Based on those problems, nurses can give support and attention for post colostomy patients. Keywords : Lived Experiences, Colostomy, Bandung